Development of Crisis Scenarios and Their Transfer to Training Models in a Simulation Centre - Vladimir BLAZEK; Martina BINDEROVÁ; Patrycja CZERNIEJEWSKA (Communications of International Proceedings, 2021)
The article presents basic approaches and selected outcomes of scientific research and practical activities carried out by authors in the area of using crisis scenarios in student training in a simulation centre. The research results were obtained as part of an international research project. Article present the results of theoretical and practical parts of the scientific-research task in question, to introduce a basic framework for the development of crisis scenarios and their transfer to a programme model of practical training simulation.
Keywords: Crisis scenarios; simulation centre; modern teaching